2021
DOI: 10.2140/pjm.2021.315.285
|View full text |Cite
|
Sign up to set email alerts
|

N∞-operads and associahedra

Abstract: We provide a combinatorial approach to studying the collection of N ∞operads in G-equivariant homotopy theory for G a finite cyclic group of prime power order. In particular, we show that for G = C p n the natural order on the collection of N ∞ -operads is in bijection with the poset structure of the (n + 1)-associahedron. We further provide a lower bound for the number of possible N ∞ -operads for any finite cyclic group G. As such, we have reduced an intricate problem in equivariant homotopy theory to a mana… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…We can put a partial order on the set of rooted binary trees with n leaves by saying that one tree is larger than another if it can be obtained from the latter by rotating a branch to the right. Balchin-Barnes-Roitzheim found that, indeed, N ∞ -diagrams for G = C p n and rooted binary trees with n + 2 leaves are isomorphic as posets [BBR19]. However, we do not wish to elaborate on this result here.…”
Section: N ∞ -Operads and N ∞ -Diagramsmentioning
confidence: 88%
See 3 more Smart Citations
“…We can put a partial order on the set of rooted binary trees with n leaves by saying that one tree is larger than another if it can be obtained from the latter by rotating a branch to the right. Balchin-Barnes-Roitzheim found that, indeed, N ∞ -diagrams for G = C p n and rooted binary trees with n + 2 leaves are isomorphic as posets [BBR19]. However, we do not wish to elaborate on this result here.…”
Section: N ∞ -Operads and N ∞ -Diagramsmentioning
confidence: 88%
“…Rubin [Rub17], Gutierrez-White [GW18] and Bonventre-Pereira [BP17] independently showed that for every such indexing system one can construct a corresponding operad. Barnes-Balchin-Roitzheim [BBR19] showed that indexing systems are equivalent to the transfer systems given in the above version of this theorem.…”
Section: N ∞ -Operads and N ∞ -Diagramsmentioning
confidence: 89%
See 2 more Smart Citations
“…Completely computing the poset I G of G-transfer systems is in general a very hard task, and it has only been done for some concrete finite groups (see [BBR21], [Rub21b], [BBPR20]). However the subposet I G of G-transfer systems closed under arbitrary homomorphisms is much easier to compute, as we will show through the following examples.…”
Section: Relating Global Transfer Systems To G-transfer Systemsmentioning
confidence: 99%